Analisis Pengendalian Kualitas pada Pengolahan Produk Lemari Tipe MC11 01 dengan Metode Statistical Process Control pada PT Alis Jaya Ciptatama - Rozi, Fahrul; Setiafindari, Widya (JURNAL TEKNIK INDUSTRI, 2022)
Abstrak PT Alis Jaya Ciptatama is a manufacturing company that produces furniture made of mahogany and teak wood into furniture items. From the production data for the MC11 01 type wardrobe in August to September 2021, it reached 800 products with a percentage of cracking defects of 5% per year then knot defects of about 4% per year, and color defects of 1% per year, far from the defect tolerance limit of 1% at PT Alis Jaya Ciptatama resulting in a re-production process and additional production costs. In this study, the method used is Statistical Quality Control where the method is used to analyze what types of defects occur in the production of MC11 01 type cabinets, then look for factors causing defects in the product and provide suggestions for improvement. This method consists of Check Sheet, Stratification, Control Map, Pareto Diagram, Cause and Effect Diagram, Scatter Diagram, and Histogram.The results of this study indicate that the factors that occur in the MC11 01 type wardrobe product are human factors, machines, methods and materials. the biggest defect is crack with a total damage of 60 products or about 50%. Then followed by wood eye defects as much as 40 or about 33%, and color defects as much as 20 or about 16.7%. Proposed improvements should be made by reviewing the machine operation process, conducting employee training, implementing a reward and punishment system and working according to the SOP for the production process.